The analyses of project management methodologies based on genome models - Бушуев, Сергей Дмитриевич; Бушуев, Денис Антонович; Ярошенко, Руслан Федорович (Technology audit and production reserves, 2016)
Many existing methodologies for project management, programs and portfolios, as a rule, are poorly structured, lacks the fullness of knowledge representation and the possibilities of comparative analysis. Development of the structure of project management methodologies based on the idea of the use of the genome code (the double helix) made it possible to create effective modeling tools in the form of ontology knowledge. Formalized genome model of project management methodologies, programs and portfolios of projects comprising methodologies algebra and a set of operations allows realizing the integration of methodologies of project management, programs and portfolios of projects under the corporate governance system. This example for modeling methodologies of project management, programs and portfolios of projects shows the possibility to carry out a comparative analysis, quickly generate or develop new methodologies adapted to the needs of organizations. The results showed the possibility of using genome models in the development of corporate project management systems, programs and portfolios. In this adaptation of the well-known methodologies and their integration into the corporate system is made in a single formal model on the principle of a hypothetical full knowledge of the system.